In situ SeO2 promoted synthesis of CdSe/PPy and Se/PPy nanocomposites and their utility in optical sensing for detection of Hg2+ ions. Issue 113 (29th October 2015) - Khanna, Pawan K.; Bhanoth, Sreenu; Dhanwe, Vaishali; Kshirsagar, Anuraj; More, Priyesh
Abstract : The reaction of selenium dioxide, a mild oxidizing agent, leads to the initiation of polymerization of pyrrole. The presence of cadmium metal can generate CdSe/PPy nanocomposites however, without it, Se/ PPy composites have been isolated. Abstract : Avoiding the use of any external oxidising agent or initiator for the polymerisation process, pyrrole was successfully polymerised to polypyrrole (PPy) using SeO2 as an internal oxidant which leads to the in situ synthesis of selenium and cadmium selenide polypyrrole (Se/PPy and CdSe/PPy) nanocomposites by chemical and microwave methods. PPy formation during the reaction was monitored by UV-Visible absorption spectroscopy. XRD measurements indicated the formation of the confirmed CdSe/PPy and Se/PPy nanocomposites. SEM images show the aggregation of small particles in the form of large globules with smooth surfaces. HRTEM images reveal the presence of spherical CdSe and Se nanoparticles homogeneously embedded in the polypyrrole matrix with interplanar distances of 0.35 nm and 0.4 nm for the (111) and (100) atomic planes, respectively. The as-synthesized CdSe/PPy and Se/PPy nanocomposites were tested for the detection of heavy metal ions. CdSe/PPy and Se/PPy successfully detected mercury ions at 25, 50 and 100 ppm. This article also describes the use of pre-synthesized Se/PPy nanocomposites as precursors for the synthesis of CdSe/PPy nanocomposites.